Pengaruh Gaya Hidup Dan Pendapatan Terhadap Keputusan Pembelian Starbucks Coffe Williem Iskandar Pancing Medan - Siagian, Abigail Ayumi; Siagian, Nalom; Sinaga, Kepler (Research and Community Service UNIVERSITAS KALBIS, 2025)
In the modern era, Indonesia's economic growth is rapid, especially due to increasing consumer spending and Starbucks has become one of the places consumers often go not only to enjoy coffee but also for their lifestyle, to be able to show it off on social media. This research aims to determine the influence of Lifestyle and Income on Purchasing Decisions among Starbucks Coffee Williem Iskandar Pancing Medan Consumers. Research shows that lifestyle (X1) has a positive and significant effect on purchasing decisions (Y), income (X2) has a positive and significant effect on purchasing decisions (Y). Meanwhile, Lifestyle (X1) and Income (X2) simultaneously have a significant effect on Purchasing Decisions (Y). The results of this research can be concluded that Lifestyle (X1) has a positive and significant effect on Purchasing Decisions (Y), Income (X2) has a positive and significant effect on Purchasing Decisions (Y), while Lifestyle (X1) and Income (X2) simultaneously have a significant effect on Purchasing Decisions (Y).